Akad dalam Transaksi Keuangan Syariah - Miftahul Janna Ritonga; Khoirudin; Muhammad Albahi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
In the Islamic financial system, akad (contract) serves as a legal foundation that distinguishes Islamic financial practices from conventional systems. An akad is not merely a contractual agreement but also reflects fundamental Sharia principles such as justice, transparency, and mutual assistance. This study aims to examine the concept of akad in Islam, the types of akad used in Islamic financial transactions, and the challenges of its implementation in Islamic financial institutions. Using a qualitative approach based on literature review, the study concludes that proper understanding and application of akad play a crucial role in maintaining the integrity and public trust in the Islamic financial system. Therefore, improving financial literacy and strengthening regulations are essential steps to support the development of a fair and sustainable Islamic economic system